Self-Report Stress Measures to Assess Stress in Adults With Mild Intellectual Disabilities—A Scoping Review - de Witte, Martina; Kooijmans, Roel; Hermanns, Maria; Hooren, Susan van; Biesmans, Kim; Hermsen, Maaike; Stams, Geert Jan; Moonen, Xavier (Frontiers in Psychology, 2021)
Stress has a major negative impact on the development of psychopathology and leads to severe physical conditions. Timely recognition of stress-related problems is therefore important, especially in client populations that appear to be more vulnerable to stress, such as people with mild intellectual disabilities (MID). Recent research on the use of physiological measures to assess stress levels shows that, in addition to these measures, self-report instruments are necessary to gain insight into the individual perception and impact of stress on daily life. However, there is no current overview of self-report stress measures that focus on the experience of stress in the present moment or in daily life. To provide an overview of the existing self-report stress measures, a scoping review was conducted. In addition, to advise clinical professionals on the use of self-report measures of stress for people with MID, the results of an expert consultation were used to refine the preliminary findings. A systematic scoping literature search resulted in a total of 13 self-reported stress measures that met the final inclusion criteria, of which three were developed specifically for assessing stress in adults with MID (GAS-ID, LI, and SAS-ID). For each included self-report stress measure, the psychometric quality, assessment procedure, and suitability for adults with MID were reported. These were supplemented by the findings from the expert consultation. Implications for clinical practice on the use of self-report stress measures, particularly for people with MID, are discussed, as well as recommendations for future research.